2007
DOI: 10.1038/nrg2167
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of sex-biased genes and sex-biased gene expression

Abstract: Differences between males and females in the optimal phenotype that is favoured by selection can be resolved by the evolution of differential gene expression in the two sexes. Microarray experiments have shown that such sex-biased gene expression is widespread across organisms and genomes. Sex-biased genes show unusually rapid sequence evolution, are often labile in their pattern of expression, and are non-randomly distributed in the genome. Here we discuss the characteristics and expression of sex-biased gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

74
1,025
5
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 834 publications
(1,108 citation statements)
references
References 87 publications
74
1,025
5
4
Order By: Relevance
“…This effect was termed "male sex drive" [12]. Male sex drive can lead to genome masculinization, which can be manifested in two main ways: 1) the existence of larger number of genes in the genome that have male-specific effects than genes that have female-specific effects, and 2) faster rates of evolution of male-biased genes than female-biased and sexunbiased genes, leading to larger divergence of male-biased genes at the levels of DNA, RNA and protein [3,13]. A masuculinized transcriptome can be, therefore, characterized by a higher proportion of male-biased genes than that of female-biased genes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was termed "male sex drive" [12]. Male sex drive can lead to genome masculinization, which can be manifested in two main ways: 1) the existence of larger number of genes in the genome that have male-specific effects than genes that have female-specific effects, and 2) faster rates of evolution of male-biased genes than female-biased and sexunbiased genes, leading to larger divergence of male-biased genes at the levels of DNA, RNA and protein [3,13]. A masuculinized transcriptome can be, therefore, characterized by a higher proportion of male-biased genes than that of female-biased genes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Sex-specific gene expression (i.e., expression exclusively in one sex) or, more commonly, sex-biased gene expression (i.e., expression predominantly in one sex), is one of the main proximate causes of phenotypic differences between the sexes in these organisms. [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Human females, for example, may experience male-pattern facial hair growth as a result of excess androgen production [5], although usually to a lesser degree than average males. The assumption that females experience fitness costs of masculinization is central to key ideas in evolutionary biology, including the evolution of sex-specific chromosomes and sex-biased gene regulation [6][7][8], the origin of sexual dimorphism [2,3,7] and maintenance of phenotypic variation in a population [9]. However, whether masculinized females actually experience social and reproductive costs in nature is surprisingly underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in species possessing sex chromosomes have revealed that differences between males and females in size, morphological features and a host of other phenotypic attributes arise mainly because of differences in gene expression profiles between the sexes [23]. The aim of this study was to determine the relative roles of ploidy level and genotype at the sex locus on gene expression patterns associated with sexual development.…”
Section: Introductionmentioning
confidence: 99%